Assessment of genetic diversity in Venezuelan rice cultivars using simple sequence repeats markers - Ghneim-Herrera, Thaura; Posso Duque, D.; Pérez Almeida, Iris B.; Torrealba N., G.T.; Pieters, AJ; Martínez Racines, César Pompilio; Tohme, Joseph M. (Elsevier, 2008)
In Venezuela, pedigree analyses indicate that the rice varieties currently under cultivation are closely related. Effective breeding programs, based on knowledge of the genetic diversity of cultivars, are needed to broaden the genetic bases of rice germplasm in the country. In this study, we used a set of 48 simple-sequence-repeat (SSR) markers to assess the genetic diversity of 11 Venezuelan rice cultivars, released by the National Rice Breeding Program between 1978 and 2007. A total of 203 alleles were detected, the number of alleles (NA) per marker ranged from 2 to 9, with an average of 4.23. The average genic diversity (H) over all SSR loci for the 18 genotypes was 0.524, ranging from 0.105 to 0.815. Positive correlations were found between H at each locus, NA, the allele size range and the maximum number of repeats. Venezuelan cultivars showed lower H (mean = 0.37) and NA (total = 124, mean = 2.58) than the whole sample. UPGMA-cluster-analysis based on genetic distance coefficients clearly separated all the genotypes, and showed that the Venezuelan rice varieties are closely related. Molecular identification of 7 Venezuelan cultivars could be done with 9 primers pairs which produced 10 genotype-specific-alleles. Although the genetic diversity was low, SSRs proved to be an efficient tool in assessing the genetic diversity of rice genotypes. Implications of the low genetic diversity detected and relatedness of Venezuelan cultivars are discussed.